Analysis of the Application of Digital Color Calibration Technology in Film Post-Production: Take the Short Film "Return to Oasis" as a Case Study - Dong, Jun; Huang, Mengting (International Journal of Culture and History, 2024)
As one of the indispensable visual elements in film and television art, color plays a key role in the visual expression and audience experience of the film, and whether the color is used properly directly affects the expression of the content of the film and television works. Through proper adjustment and control of color in film and television post-production, the film can better convey the story emotion and enhance the audience’s visual feeling of the film. Therefore, digital color correction is a very important link in film and television post-production. In the creation of short films, screen color can be said to be one of the more intuitive and powerful means of expression, and the application of digital color correction technology plays a key role in the presentation of short films. The primary color correction can make up for the deficiency of the previous shooting materials, such as correcting exposure and color deviation, and the secondary color adjustment can give the short films a unique visual style and create a specific emotional atmosphere. In addition, adjusting the color of the picture in line with the story plot can directly affect the emotions and feelings of the audience, which not only makes the short film more appealing, but also helps the creator to better convey the theme of the film. This paper mainly combines the application of digital color correction technology in the post-production of the graduation project short film "Return Oasis", firstly introduces the basic principle and application scope of digital color correction technology, and then describes in detail the specific application and influence of digital color correction technology in the production process of "Return Oasis" short film, as well as the problems encountered in the production process and solutions. Finally, the design process of "Return to Oasis" is briefly described, and the design process of the work is reflected and summarized.